Новый в фауне СССР подвид прыткой ящерицы — Lacerta agilis euxinica Fuhn et Vancea, 1964 (Reptilia, Lacertidae) - Котенко, Т.И.; Таращук, С.В. (Вестник зоологии, 1982)
Three subspecies of Lacerta agilis are established for the South Ukraine: chersonersis, exigua and euxinica. The latter,previously known only inRomania, i sreportedfor the first time for U.S.S.R. fauna. Ukrainian populations o fL. agilis euxinica are described with reference to their general occurrence, geographic distribution, habitat and overlapping with ssp. exigua.